1997
DOI: 10.1530/eje.0.1370234
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and nicotinamide have similar effects in maintaining residual beta cell function in recent onset insulin-dependent diabetes (the IMDIAB IV study)

Abstract: Objective: Protection of residual beta cell function at the time of diagnosis of insulin-dependent diabetes mellitus (IDDM) by intensive insulin therapy and the addition of nicotinamide (NA) has been established. The objective of this study was to evaluate the effect of a free oxygen radical scavenger such as vitamin E (Vit E) on residual beta cell function and parameters of metabolic control in patients with recent onset IDDM undergoing intensive insulin therapy. Design: The effect of Vit E was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 28 publications
2
23
0
2
Order By: Relevance
“…Furthermore, serum tocopherol levels were shown to be inversely correlated with the risk of developing type 1 diabetes mellitus in humans (51). In a one year prospective clinical trial, vitamin E was given to newly diagnosed type 1 diabetes mellitus patients receiving intensive insulin treatment (28). In this study, a comparison was made with nicotinamide, and it turned out that the radical scavenger vitamin E showed beneficial effects equal to nicotinamide in preserving ␤-cell function in terms of glycosylated hemoglobin and C-peptide levels, which were significantly improved compared to patients on intensive insulin therapy only (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, serum tocopherol levels were shown to be inversely correlated with the risk of developing type 1 diabetes mellitus in humans (51). In a one year prospective clinical trial, vitamin E was given to newly diagnosed type 1 diabetes mellitus patients receiving intensive insulin treatment (28). In this study, a comparison was made with nicotinamide, and it turned out that the radical scavenger vitamin E showed beneficial effects equal to nicotinamide in preserving ␤-cell function in terms of glycosylated hemoglobin and C-peptide levels, which were significantly improved compared to patients on intensive insulin therapy only (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a one year prospective clinical trial, vitamin E was given to newly diagnosed type 1 diabetes mellitus patients receiving intensive insulin treatment (28). In this study, a comparison was made with nicotinamide, and it turned out that the radical scavenger vitamin E showed beneficial effects equal to nicotinamide in preserving ␤-cell function in terms of glycosylated hemoglobin and C-peptide levels, which were significantly improved compared to patients on intensive insulin therapy only (28). Our present results concur with these reports, in that we detected a partial (approx 50%) preventive effect of ␥-tocopherol, but not ␣-tocopherol, on RINm5F cells exposed to IL-1␤ or NO.…”
Section: Discussionmentioning
confidence: 99%
“…The network includes registration of new cases (Eurodiab ACE) (ages 0 -15 years) and participation in clinical trials (IMDIAB) (ages 5-35 years) aimed at protecting residual b-cell function (6,7). Previous reports have focused on agebased differences in clinical presentation of type 1 diabetes (2,8,9), but data on sex-based effects on residual b-cell function and clinical presentation have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators suggested combining the remedies for a possible synergistic effect; however, a control group of patients treated solely with insulin, as seen in earlier studies by the same group, was lacking in this trial. 16 In the IMDIAB IX study by Crino and colleagues, 17 discussed later in the section on vitamin E, children with new-onset type 1 diabetes were treated with either vitamin E or nicotinamide in addition to insulin for 2 years. No significant differences were found between c-peptide and HbA 1c levels, and the vitamin E group had a higher insulin requirement than the nicotinamide group.…”
Section: Nicotinamidementioning
confidence: 99%